Experimental Justification of Invaginative Compressive Intestinal Anastomosis Modeling - Melnik, V.M.; Polovnikov, I.I.; Poyda, O.I.; Shepetko, Ye.M. (Science and Innovation, 2024)
Introduction. Modern circular staplers do not solve the problem of size-mismatched anastomosis. This mismatch leads to deformation of the anastomosis and disrupts healing processes, which often entails complications. Therefore, the problem of stapling size-mismatched anastomosis is actual and needs to be solved. Problem Statement. Development and testing of device that forms anatomical and functional justified invaginative anastomosis of mismatched intestines offcuts on experimental animals. Purpose. Experimental improvement of the technique for invaginative anastomosis of mismatched intestines offcuts modeling using a new device designed by the authors. Materials and Methods. New device for invaginative compressive intestinal anastomosis modeling of mismatched intestines offcuts has been designed. In experiment conditions, methods for the most complicated ileocolic, ileorectal, colorectal anastomoses have been tested out on animals using the new designed device. Results. Uncomplicated more physiologic healing process of the intestinal anastomosis and advisability of using the new designed device in clinics have been shown. Conclusions. Compressive junction method is sufficient for intestinal anastomosis formation, because it provides physiologic process of reparation. The study of invaginative compressive intestinal anastomosis formed in experiment conditions between mismatched intestinal offcuts using the new designed device has shown its anatomical and physiological usability and applicability in clinical practice.